2013
DOI: 10.3174/ajnr.a3806
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Sinus Stenting for Pseudotumor Cerebri: A Cost Comparison with CSF Shunting

Abstract: BACKGROUND AND PURPOSE:Transverse sinus venous stent placement has been shown to lower intracranial pressure in patients with venogenic pseudotumor cerebri and to reverse, or at least stabilize, its symptoms and signs. There have been no studies comparing the cost of venous stenting with the time-honored treatment for pseudotumor cerebri-CSF shunting. The purpose of this study was to compare the cost of trasverse sinus stenting versus CSF shunting for the treatment of pseudotumor cerebri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…These results appear much more favorable than those reported for shunting in IIH in which there is a 75% failure rate at 2 years for VP shunts and an 86% failure rate at 18 months for LP shunts [5]. Along these lines, Ahmed et al [33] recently conducted a cost analysis for shunting versus venous sinus stenting in the treatment of IIH, and found that venous stenting significantly reduced the cost per 100 procedures compared with shunting. Although the cost of each individual procedure was similar, the additional cost resulted from a far greater number of shunt procedures performed per patient.…”
Section: Discussionmentioning
confidence: 65%
“…These results appear much more favorable than those reported for shunting in IIH in which there is a 75% failure rate at 2 years for VP shunts and an 86% failure rate at 18 months for LP shunts [5]. Along these lines, Ahmed et al [33] recently conducted a cost analysis for shunting versus venous sinus stenting in the treatment of IIH, and found that venous stenting significantly reduced the cost per 100 procedures compared with shunting. Although the cost of each individual procedure was similar, the additional cost resulted from a far greater number of shunt procedures performed per patient.…”
Section: Discussionmentioning
confidence: 65%
“…Ahmed et al 53 reported that in their health care system in Australia, the cost of the initial dural venous sinus stent placement was similar to the cost of the initial CSF flow-diversion procedure; however, when one took into account the cost of revisions, the total cost of CSF flow diversion was 5 times higher. Although CSF flow diversion is commonly performed, the literature regarding outcomes and high rates of revision does not compare favorably with recent data on venous sinus stent placement when using strict patient selection, dual antiplatelet therapy, and modern devices.…”
Section: Discussionmentioning
confidence: 99%
“…97,98,101,102,107 -109 Intracranial MR or CT venograms are performed to exclude dural sinus thrombosis or stenosis. In cases that are positive for either venous sinus thrombosis or stenosis, it is unclear as to whether the increased intracranial pressure resulted in compression of the dural venous sinuses leading to these findings, or if the thrombosis or stenosis led to impaired CSF resorption and increased pressure 98,99,110 (Fig. 13).…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 97%